ACCESS: an empirically-based framework developed by the International Nursing CASCADE Consortium to address genomic disparities through the nursing workforce - Katapodi, Maria C.; Pedrazzani, Carla; Barnoy, Sivia; Dagan, Efrat; Fluri, Muriel; Jones, Tarsha; Kim, Sue; Underhill-Blazey, Meghan L.; Uveges, Melissa K.; Dwyer, Andrew A. (Frontiers in Genetics, 2024)
Efforts are needed across disciplines to close disparities in genomic healthcare. Nurses are the most numerous trained healthcare professionals worldwide and can play a key role in addressing disparities across the continuum of care. ACCESS is an empirically-based theoretical framework to guide clinical practice in order to ameliorate disparities in genomic healthcare. The framework was developed by the International Nursing CASCADE Consortium based on evidence collected between 2005 and 2023 from individuals and families of various ethnic backgrounds, with diverse hereditary conditions, and in different healthcare systems, i.e., Israel, Korea, Switzerland, and several U.S. States. The components of the framework were validated against published scientific literature. ACCESS stands for Advocating, Coping, Communication, cascadE Screening, and Surveillance. Each component is demonstrated in concrete examples of clinical practice within the scope of the nursing profession related to genomic healthcare. Key outcomes include advocacy, active coping, intrafamilial communication, cascade screening, and lifelong surveillance. Advocacy entails timely identification of at-risk individuals, facilitating referrals to specialized services, and informed decision-making for testing. Active coping enhances lifelong adaptation and management of disease risk. Effective intrafamilial communication of predisposition to hereditary disease supports cascade testing of unaffected at-risk relatives. Lifelong surveillance is essential for identifying recurrence, changes in health status, and disease trajectory for life-threatening and for life-altering conditions. ACCESS provides a standardized, systematic, situational, and unifying guide to practice and is applicable for nursing and for other healthcare professions. When appropriately enacted it will contribute towards equitable access to genomic resources and services.